Anti‐inflammatory and analgesic activity of carnosol and carnosic acid in vivo and in vitro and in silico analysis of their target interactions. (8th August 2016) - Maione, Francesco; Cantone, Vincenza; Pace, Simona; Chini, Maria Giovanna; Bisio, Angela; Romussi, Giovanni; Pieretti, Stefano; Werz, Oliver; Koeberle, Andreas; Mascolo, Nicola; Bifulco, Giuseppe
Abstract : Background and Purpose: The diterpenoids carnosol (CS) and carnosic acid (CA) from Salvia spp. exert prominent anti‐inflammatory activities but their molecular mechanisms remained unclear. Here we investigated the effectiveness of CS and CA in inflammatory pain and the cellular interference with their putative molecular targets. Experimental Approach: The effects of CS and CA in different models of inflammatory pain were investigated. The inhibition of key enzymes in eicosanoid biosynthesis, namely microsomal prostaglandin E2 synthase‐1 (mPGES‐1) and 5‐lipoxygenase (5‐LO) was confirmed by CS and CA, and we determined the consequence on the eicosanoid network in activated human primary monocytes and neutrophils. Molecular interactions and binding modes of CS and CA to target enzymes were analyzed by docking studies. Key Results: CS and CA displayed significant and dose‐dependent anti‐inflammatory and anti‐nociceptive effects in carrageenan‐induced mouse hyperalgesia 4 h post injection of the stimuli, and also inhibited the analgesic response in the late phase of the formalin test. Moreover, both compounds potently inhibited cell‐free mPGES‐1 and 5‐LO activity and preferentially suppressed the formation of mPGES‐1 and 5‐LO‐derived products in cellular studies. Our in silico analysis for mPGES‐1 and 5‐LO supports that CS and CA are dual 5‐LO/mPGES‐1 inhibitors. Conclusion and Implications: In summary, we propose that the combined inhibition of mPGES‐1 and 5‐LO by CS and CA essentially contributes to the bioactivity of these diterpenoids. Our findings pave the way for a rational use of Salvia spp., traditionally used as anti‐inflammatory remedy, in the continuous expanding context of nutraceuticals. Linked Articles: This article is part of a themed section on Principles of Pharmacological Research of Nutraceuticals. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v174.11/issuetoc